Comparative analysis of the hemostasis system of cancer patients with thrombotic complications - Bodnar, P. Ya. (Modern medical technology, 2021)
Surgical treatment of female genital cancer remains a rather difficult task in gynecological practice due to the possibility of thrombotic complications. It is important to study the features of hemostasis in such patients for the practical application of this knowledge. The aim of the study was to scientifically substantiate the features of hemostasis in patients with female genital cancer. Study materials: 103 patients with genital cancer who were treated. The purpose of the study. Coagulogram, colorimetry, others. Results of the research. As a result of a blood test, it was found that the initial level of hemoglobin in patients with thrombotic complications after surgery decreased by 12%, in patients without thrombotic complications – by 14%. The average platelet count in patients with thrombotic complications decreased by 11,50%, in patients without thrombotic complications – 8,12%. The level of leukocytes in patients with thrombotic complications – increased by 21,05%, in patients without thrombotic complications – 30,30%. In the study of hemostasis, it has been found that surgery in patients with female genital cancer causes a pronounced activation of the hemostasis system, especially in patients with thrombotic complications. In patients with thrombotic complications there is a more pronounced activation of intravascular coagulation on the background of a significant decrease in the level of antigen III than in patients without thrombotic complications. The level of fibrinogen in patients with thrombotic complications in the preoperative period was significantly higher by 16,3% than in patients without thrombotic complications; there was a decrease in fibrinogen levels in the early postoperative period; from the third day after surgery, fibrinogen levels increased in patients without thrombotic complications. There was also a significant reduction in activated partial thromboplastin time in patients with thrombotic complications. The number of soluble complexes of fibrin monomers increased to higher values in patients with thrombotic complications. Conclusion. In the study of hemostasis, it has been found that surgery in patients with female genital cancer causes marked activation of the hemostasis system, especially in patients with thrombotic complications.